Effect of a High-Intensity Tandem Bicycle Exercise Program on Clinical Severity, Functional Magnetic Resonance Imaging, and Plasma Biomarkers in Parkinson's Disease - Segura, Carolina; Eraso, Mauricio; Bonilla, Javier; Mendivil, Carlos O.; Santiago, Giselle; Useche, Nicolás; Bernal-Pacheco, Oscar; Monsalve, Guillermo; Sanchez, Laura; Hernández, Enrique; Peláez-Jaramillo, Maria José; Cárdenas-Mojica, Allison (Frontiers in Neurology, 2020)
The optimal modality, intensity, duration, frequency and dose-response of exercise as a therapy for Parkinson´s Disease (PD) are insufficiently understood. Objective: To assess the impact of a high-intensity tandem bicycle program on clinical severity, biomarkers and fMRI in PD. Methods: A single-center, parallel-group clinical trial was conducted. Thirteen PD patients aged 65 or younger were divided in two groups: A control group and an intervention group that incorporated a cycling program at 80% of each individual's maximum HR (≥80 revolutions/min), three times a week, for sixteen weeks. Both groups continued their conventional medications for PD. At baseline and at the end of follow up, we determined in all participants the Unified Parkinson´s Disease Rating Scale, anthropometry, VO2max, PD biomarkers and fMRI. Results: VO2max improved in the IG (+5.7 mL/Kg/min), while it slightly deteriorated in the CG (-1.6 mL/Kg/min) (p=0.041). Mean UPDRS went down by 5.7 points in the IG and showed a small 0.9 points increase in the CG (p=0.11). fMRI showed activation of the right fusiform gyrus during the motor task and functional connectivity between the cingulum and areas of the frontal cortex, and between the cerebellar vermis and the thalamus and posterior temporal gyrus. Plasma Brain-Derived Neurotrophic Factor (BDNF) levels increased more than 10-fold in the IG, and decreased in the CG (p=0.028). Larger increases in plasma BDNF correlated with greater decreases in UPDRS (r=-0.58, p=0.04). Conclusions: Our findings suggest that high-intensity tandem bicycle improves motor function, biochemical and functional neuroimaging variables in PD patients.